Deskryptory BN i Język Haseł Przedmiotowych BN ? próba konfrontacji = Descriptors of the National Library and the Language of Subject Headwords ? an attempt at a confrontation - Chocianowska-Sidoruk, Maja; Czarnecka, Elżbieta (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The authors of this article took up the topic of the National Library descriptors as a new information and search language. The first part discusses an open conference held at the National Library in April 2015. At the conference, descriptors were proposed as a new tool for the development of library collections and participants were informed about the decision to implement a model of entity connections to the ISBD standard from the RDA cataloguing standard. The second part deals with granulation: i.e. simplifications in the form of descriptors and their relationship with the introduction of the RDA standard. In the next part the authors discuss the principles for creating descriptors, their types, and indexing in the fields of the bibliographic record and the model record. They also discuss the essence of changes in the bibliographic description related to the introduction of new fields, and analyze detailed changes pertaining to the selection principles and the creation of passwords, currently descriptors. To this end, they confront instructions regarding the principles for creating personal, corporate and geographic descriptors with appropriate instructions for the passwords of the National Library. In summing up, the authors pose a question about the validity of changes from the Language of Subject Headwords of the National Library (JHP) into the Descriptors of the National Library (DBN), and emphasize their sense by linking them with, among other things, a simplified descriptor form, the possibility of transition from a pre-coordinated system to a post-coordinated system, and a high level of search efficiency.
Keywords: Deskryptory Biblioteki Narodowej; język haseł przedmiotowych Biblioteki Narodowej; dane; języki informacyjne; Bibliotekarstwo; Descriptors of the National Library; Languageof Subject Headwords of the National Library; data; information languages; librarianship